Sub-7-nm textured ZrO2 with giant ferroelectricity. (15th February 2021) - Huang, Kuei-Wen; Yi, Sheng-Han; Jiang, Yu-Sen; Kao, Wei-Chung; Yin, Yu-Tung; Beck, David; Korolkov, Vladimir; Proksch, Roger; Shieh, Jay; Chen, Miin-Jang
Abstract: An ~6.5 nm pure ZrO2 thin film with a giant ferroelectric remanent polarization ( P r ) of ~50 μ Ccm − 2 and an effective piezoelectric coefficient ( d 33 ) of 7−9 pm/V is reported. The film was prepared on a (111)-oriented Pt electrode using plasma-enhanced atomic layer deposition at 300 °C, followed by annealing at 400 °C, and exhibited a preferred orientation of the orthorhombic (111) planes in the in-plane direction. The P r value of ~50 μ Ccm − 2 is the largest reported to date for both perovskite and fluorite nanoscale ferroelectric thin films (< 120 nm) on a Pt electrode. Furthermore, the processing temperature of 300−400 °C is the lowest reported to date to produce a P r of ~50 μ Ccm − 2 in nanoscale ferroelectrics on a Pt electrode. The giant P r, ascribed to the preferred crystal orientation, was confirmed by the positive-up negative-down (PUND) polarization measurement with a long delay time to allow the relaxation of polarization. The effective d 33 was obtained using piezoresponse force microscopy with an interferometric displacement sensor to minimize the frequency-dependent artifacts and the effects of cantilever dynamics. The low-temperature preparation of the textured ZrO2 ultrathin film with a giant P r is extremely advantageous for device scaling and process integration in advanced nanoelectronics. Graphical abstract: Image, graphical abstract